2005
DOI: 10.1074/jbc.m412593200
|View full text |Cite
|
Sign up to set email alerts
|

DRO1, a Gene Down-regulated by Oncogenes, Mediates Growth Inhibition in Colon and Pancreatic Cancer Cells

Abstract: Neoplastic progression in human tissues appears to be paralleled by a series of genetic and epigenetic alterations. In human colorectal cancers, defect Wnt/␤-catenin/T-cell factor and RAS/RAF signaling pathways have a major contributing role in tumor initiation and progression. To date, much of the research on the consequences of ␤-catenin activation has been focused on genes whose expression is believed to be activated by ␤-catenin-associated T-cell factor-dependent transcription. Little is known about genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 59 publications
2
87
2
Order By: Relevance
“…Despite the strong prediction that Ccdc80 contains an N-terminal signal peptide sequence, published experiments had yielded contradictory results (23,25,47) prompting us to reexamine whether Ccdc80 is indeed a secreted protein. We found that human Ccdc80 ectopically expressed in HEK293T and, more importantly, endogenous Ccdc80 in 3T3-L1 adipocytes are secreted proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the strong prediction that Ccdc80 contains an N-terminal signal peptide sequence, published experiments had yielded contradictory results (23,25,47) prompting us to reexamine whether Ccdc80 is indeed a secreted protein. We found that human Ccdc80 ectopically expressed in HEK293T and, more importantly, endogenous Ccdc80 in 3T3-L1 adipocytes are secreted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Although Ccdc80 is highly conserved between species, no close homologs are found in either human, mouse, or rat genomic sequences (22,23). Using real-time reverse transcription-PCR, we found that mouse Ccdc80 is highly expressed in white adipose tissue (WAT) with significantly lower mRNA levels in other tissues, including brown adipose tissue (BAT) (Fig.…”
Section: Identification Of Ccdc80 As a Gene Encoding A Potential Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results showed negligible presence of high-molecular-weight forms of CCDC80 in human adipose tissue depots and a only small amount in control plasma, these species are consistently observed in cultured murine adipocytes (7) and in cells ectopically expressing CCDC80 (7,22). We therefore analyzed total CCDC80 protein in cultured human SGBS cells, in confluent preadipocytes, and in differentiating and mature adipocytes.…”
Section: Ccdc80 Expression In Human Sgbs Adipocytesmentioning
confidence: 99%
“…In this study, we also included the RK3E cell line because it has been widely used to assess transformation ability of potential oncogenes. [27][28][29][30][31][32][33] Cells transfected with BRAF V600E were grown in 96-well plates at a density of 3000 cells per well. As controls, the empty vector and BRAF WT vector were also transfected into the cells.…”
Section: Cell Growth Assaymentioning
confidence: 99%